Islam and Disaster Risk Reduction: The Role of Local Religious Leaders in Transforming Communities in Gampong Deah Glumpang, Banda Aceh - Fatimahsyam, Fatimahsyam (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
The traditional perspective that perceives disasters as acts of divine destiny underwent a critical transformation following the 2004 Indian Ocean earthquake and tsunami. This classical view, which rendered communities passive in the face of disaster risks, has been progressively replaced by a more proactive understanding. Religious scholars (ulama) have played a pivotal role in fostering this transformation, encouraging communities to adopt active, participatory, and organized approaches to disaster risk reduction (DRR). This qualitative field study, conducted in Gampong Deah Glumpang, Banda Aceh, investigates two primary aspects: the management approaches of DRR programs implemented in the village and their impact on enhancing the community’s understanding and participation in building disaster resilience two decades after the tsunami. The findings reveal that local religious leaders significantly influenced the community’s shift from perceiving disasters as unchangeable divine decrees to recognizing the importance of proactive mitigation efforts. Through religiously grounded narratives, these leaders mobilized the community to actively engage in DRR initiatives, including risk mapping, contingency planning, and environmental conservation, as facilitated by the Banda Aceh Disaster Management Agency (BPBD), the International Organization for Migration (IOM), and the Indonesian Red Cross (PMI). The integration of religious teachings with DRR frameworks proved effective in transforming perceptions, strengthening social cohesion, and fostering inclusivity, particularly for vulnerable groups.